(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article examines the relationship between the state of the intestinal microbiota and the regulation of glucose metabolism. It highlights the mechanisms by which intestinal microbes affect insulin sensitivity, inflammation, and energy homeostasis. It describes the factors that change the composition of the microbiota and their consequences for the risk of developing type 2 diabetes. It presents modern methods for correcting the intestinal microflora and the possibilities of using probiotics and prebiotics in the prevention of carbohydrate metabolism disorders. It emphasizes the potential of the microbiota as a therapeutic target in the future.